Dampak Rokok terhadap Ekspresi Matrix Metalloproteinase-9 (MMP-9) dan Hubungannya dengan Penyakit Paru Obstruktif Kronik: Tinjauan Sistematik - Nugraha Putra, Oki; Anabella, Rantie Queenza; In’ami, Istiara Nafida; Nur Hasibullah Ma, Akbar Yuniar; Purwanto, Ryo Wahyu (Cermin Dunia Kedokteran, 2026)
Introduction: Cigarette smoke can induce the expression of matrix metalloproteinase-9 (MMP-9) and is associated with COPD. This review aims to assess the impact of cigarette smoke on MMP-9 expression and its association with COPD. Methods: This study is a scoping review using articles analyzing the impact of cigarette smoke on MMP-9 levels in COPD patients from the PubMed and Google Scholar databases. A total of 11 articles that met the inclusion criteria were used in this review, of which 6 studies used serum or plasma, 1 study used bronchoalveolar lavage (BAL), and 4 studies used sputum samples to measure MMP-9 levels. Results: Overall, MMP-9 levels were found to be significantly greater in COPD patients who smoked compared to non-smoking COPD patients and healthy individuals. MMP-9 levels increased with increasing severity of COPD. MMP-9 levels correlated with the smoking index. Conclusion: More cigarette consumption will further increase MMP-9 levels. Smoking increases MMP-9 expression and is associated with COPD.